Digital technologies as a tool for identification the authorship of sacred sculpture - Bitko, Sanita (Landscape Architecture and Art, 2023)
Latvian sculptures created before the mid-19th century are located mainly in churches, not in museum collections. The most serious obstacle to research of Latvian art in the given period is lack of pertinent documentary material. As a result, Latvian art historians have mostly studied the sculptures for which written sources are available. This article will offer solutions for further research in cases when written sources are limited or altogether unavailable. How much and what can be discovered using digitisation solutions? The study of the sculptures of the Biķernieki Church in Riga provides a paradigmatic case for further research with the help of digitisation. In 1967, when the congregation of the Biķernieki Church was forced to abandon the church, the sculptures were transferred to museums. Today they can be seen in the exhibition of the Rundāle Palace Museum. The scant extant documentary evidence does not allow us to establish the authorship of the sculptures or the time of their creation with certainty. The study discussed in the article shows the importance of digitisation in art history research. The current research is based on 3D models of the sculptures of the Biķernieki Church obtained using 3D scanning technology. Supplementing them with high-resolution photographs and other digital solutions can confirm or, on the contrary, refute assumptions about their authorship and creation made by historians so far. The article outlines the methods used to identify stylistic influences on the sculptures of the Biķernieki Church, suggesting that they may have been modelled after similar sculptures in Gdańsk (Danzig) and Dresden and even after certain antique sculptures. The graphic methods used in the research have made it possible to precisely identify the style of execution of a single sculptor in several churches in Riga.